Sonication amplitude and processing time influence the cellulose nanocrystals morphology and dispersion. Issue 1 (2nd January 2020) - Shojaeiarani, Jamileh; Bajwa, Dilpreet; Holt, Greg
Abstract: The application of bio-based materials is becoming impellent owing to the increasing demand for alternatives to petroleum-based analogs. In this regard, cellulose nanocrystals (CNCs) with unique properties have received a significant interest, while their hydrophilic character poses a challenge to their commercial applications. Ultrasonication treatment is one of the most commonly used methods to improve CNCs' dispersion in different solvents and polymer matrices. In this work, the effectiveness of ultrasonication treatment in the dispersion of CNCs in a water-soluble polymer (polyvinyl alcohol, PVA) was studied. An aqueous suspension of polyvinyl alcohol and CNCs was prepared using different ultrasonication times and amplitudes. The morphology, particle size and dispersion of CNCs were studied using X-ray diffraction, transmission electron microscopy, and dynamic light scattering. The results indicated that with increase in the sonication amplitude, there was a substantial decrease in nanoparticle length, while long sonication times gently affected the nanoparticle length. Furthermore, improved dispersion was observed in samples prepared using longer sonication time. Graphical Abstract: